Awareness of isotretinoin use and safety in Saudi Arabia: A nationwide cross-sectional study - Abdullah A Alshehri; Bander A Althobaiti; Wael Y Khawagi; Kevin D Murphy (Elsevier, 2023)
Introduction: Acne is a prevalent skin condition that affects numerous adolescents and adults worldwide. The most effective treatment for acne is isotretinoin, but its usage is associated with a wide range of adverse effects, and regular monitoring is necessary. Hence, appropriate usage with awareness of potential side effects is crucial. This study aimed to assess the knowledge and awareness of isotretinoin use and safety among individuals with acne in Saudi Arabia. Methods: A national cross-sectional survey was conducted through an online self-administered questionnaire distributed via social media platforms. The questionnaire consisted of 27 questions in multiple-choice and Likert scale formats, covering demographics, patient awareness of isotretinoin use and side effects, satisfaction with clinical consultation and information provided. Descriptive statistics were used to summarize data. Results: 1315 participants completed the survey, of which most were female (74.1%), single (67.5%), and aged 18-25 years (48.9%). Dryness and teratogenicity were the most commonly known side effects of isotretinoin use (85.5% and 64.9% respectively). However, most participants were unaware of other side effects, such as psychiatric disorders (62.9%), altered liver enzyme concentrations (65.2%), hyperlipidemia (68.1%), anemia (92.4%), and decreased platelet count (96%). Moreover, 36% of sexually active females initiated isotretinoin without contraception. Regarding satisfaction with the information provided during clinical consultation, 63.2% of participants were very satisfied or satisfied. Doctors were the primary source of information (86.8%), followed by the internet (17.8%). Only 45% were informed to avoid blood donation during and after treatment for at least two months. Conclusion: The study highlights the significance of providing patients with comprehensive information about the potential side effects of isotretinoin, including the need to use contraception and avoid blood donation during and after treatment. Effective communication between physicians and patients is critical in ensuring the safe and effective use of isotretinoin.